TRADISI PENYELENGGARAAN AQIQAH MASYARAKAT PURWOREJO (Kajian Living Hadis) - Siti Aminah (IAIN Kediri, 2018)
Aqiqah is a religious ceremony that is very common in Muslim communities. The ritual is the slaughter of goat in the seventh day of the baby birth. Aqiqah has become a tradition in our communities, but in the practice there are many differences. The main factor of the differences is the different understanding and perception toward hadith about aqiqoh. This article discusses about the understanding of Purworejo community, Sanan Kulon, Blitar district toward aqiqah hadith and the implementation by using sociology-history approach. The research finding shows that Purworejo community conducts aqiqah tradition not only following the previous tradition but also having knowledge that it is a direction of the Prophet. The understanding of Purworejo community toward the hadith is not textually. They understand the aqiqah hadith contextually. Keywords: Aqiqah, hadith, textual, contextual